2004
DOI: 10.1159/000079972
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Dysfunction of the Frontal Lobe in Schizophrenia

Abstract: Localized in vivo proton magnetic resonance spectroscopy (MRS) was performed to evaluate metabolic alterations in the right and left frontal lobe before and after antipsychotic treatment of schizophrenic patients (n = 24) and a group of healthy normal subjects (n = 20). Proton metabolic ratios obtained from the 8 cm3 voxels in the right and left frontal lobes were compared with the clinical assessment for each subject. There was no significant difference in the metabolic ratios between the right and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
2
16
1
Order By: Relevance
“…Our study did not achieve enough power to detect the previously reported 15% increase in glutamine (p = 0.03) [13] in schizophrenia versus control. Although our study did not affirm the findings of a recent study [26] in which large decreases in Cr (60%, p < 0.001) and Cho (54%, p < 0.001) in the DPFC were reported, it did agree with prior studies in which no changes in Cr (left anterior cingulate, [13]) or Cho (left anterior cingulate [13], frontal lobe [24], DPFC [25]) were observed. Similar to GSH in the medial prefrontal cortex versus the anterior cingulate, the changes measured in the DPFC may not have been reflected in the anterior cingulate.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study did not achieve enough power to detect the previously reported 15% increase in glutamine (p = 0.03) [13] in schizophrenia versus control. Although our study did not affirm the findings of a recent study [26] in which large decreases in Cr (60%, p < 0.001) and Cho (54%, p < 0.001) in the DPFC were reported, it did agree with prior studies in which no changes in Cr (left anterior cingulate, [13]) or Cho (left anterior cingulate [13], frontal lobe [24], DPFC [25]) were observed. Similar to GSH in the medial prefrontal cortex versus the anterior cingulate, the changes measured in the DPFC may not have been reflected in the anterior cingulate.…”
Section: Discussioncontrasting
confidence: 99%
“…Brain GSH content has also been shown to change in human PD [23] (37-89% decreases) and developing rat cortex [10] (60% increase). Several studies of schizophrenia have reported the following decreases in NAA content, most of which would have been sizable enough for detection in our study: 31% (p = 0.005) in prefrontal cortex [9], 12% (p = 0.005) in frontal lobe [24], 17% (p < 0.05) [25] and 56% (p < 0.001) [26] in dorsolateral prefrontal cortex (DPFC). Of these, the one that showed the greatest decrease in NAA [26] was the only one that corrected for varying gray matter content, which has been shown to improve ability to detect changes [27].…”
Section: Discussionmentioning
confidence: 51%
“…As discussed above, these findings may be the expression of underlying changes in ATP expenditure and availability, oxygen consumption, and/or glutamatergic activity in BPD. Similar changes in NAA have also been described in schizophrenia (mainly in prefrontal cortex) (Pae et al, 2004;Rowland et al, 2001;Theberge et al, 2004), indicating that some common pathophysiological mechanisms (either as cause or sequelae), may be present in these conditions. However, follow-up studies observing NAA changes after mood stabilizer treatment (described below) may indicate the particular relevance of this metabolite variation in BPD.…”
Section: Could Impairments Of Cellular Plasticity and Resilience Be Asupporting
confidence: 69%
“…There have been reports that NAA levels are preserved rather than decreased by atypical antipsychotic treatments (22,29,30). Many reports show little impact of medication on NAA levels (26,31). The reduction in NAA with disease progression may be consistent with the reduction in brain regional volume and disease progression (27,32,33).…”
Section: N-acetyl Aspartate (Naa)mentioning
confidence: 95%
“…Because of its ability to monitor levels of phospholipid, phosphomonoesters and phosphodiesters, which appear to change in some psychiatric disorders, 31 P MRS has the potential to monitor those levels as biomarkers of disease and treatment of the disease. However, until the locations and directions of the changes are more uniformly established, the use of 31 P MRS as such a marker will be limited.…”
mentioning
confidence: 99%